Consumo alimentar de pacientes submetidos a cirurgia de colecistectomia - Silva, Flávia Nascimento da (My University, 2019)
The incidence of biliary disease is increasing and represents an overload in health systems around the world. One situation that can lead to the formation of gallstones is the redundant intake of hypercaloric and hyperlipidic diet. Dietary protection factors include a high-fiber diet that speeds up intestinal transit and ingestion of some dietary components such as calcium, magnesium, vitamin C and moderate alcohol consumption. The objective of this study was to evaluate the patients' previous eating habits in the postoperative period of cholecystectomy. Methods: The study is characterized by a cross-sectional descriptive nature.The food intake was evaluated through a food frequency questionnaire, the analyzed nutrients were classified by the Dietary Reference Intakes (DRIs), 2002. The nutritional consumption was estimated using the Dietbox® nutritional assessment software. Results: The patients' diet was classified according to energy, with 42.9% patients with hypocaloric diet representing 6, 7,1% patient with normocaloric diet representing 1 and 50% patients with hypercaloric diet representing 7 of them. In micronutrients and saturated fat 50% of these patients reached the recommendation of fiber, vitamin C and saturated fat (7), 28,6% of the patients reached the recommendations of calcium (4) and 35,7% of the patients reached the recommendations of magnesium (5) Conclusion: Each patient should be evaluated individually, with dietary adjustment to their needs and clinical conditions. [resumo fornecido pelo autor]
A incidência de doença do cálculo biliar está aumentando e representa uma sobrecarga nos sistemas de saúde em todo o mundo. Uma situação que pode levar à formação de cálculos biliares é a redundante ingestão de dieta hipercalórica e hiperlipídica. Os fatores de proteção dietéticos incluem uma dieta rica em fibras, que acelera o trânsito intestinal e a ingestão de alguns componentes da alimentação como cálcio, magnésio, vitamina C e o consumo moderado de álcool. O objetivo deste estudo foi avaliar os hábitos alimentares prévios dos pacientes no pós-operatório de colecistectomia. Métodos: O estudo caracteriza-se por ser de delineamento transversal de natureza descritiva. O consumo alimentar foi avaliado através de um questionário de frequência alimentar, os nutrientes analisados foram classificados pelas Dietary Reference Intakes (DRIs), 2002. A estimativa do consumo de nutrientes foi realizada com utilização do software de avaliação nutricional Dietbox®. Resultados: A dieta dos pacientes foi classificada conforme a energia, tendo 42,9% dos pacientes com dieta hipocalórica representando 6, 7,1% dos pacientes com dieta normocalórica representando 1 e 50% dos pacientes com dieta hipercalórica representando 7 dos mesmos. Nos micronutrientes e gordura saturada 50% destes pacientes atingiram a recomendação de fibras, vitamina C e gordura saturada (7), 28,6% dos pacientes atingiram as recomendações de cálcio (4) e 35,7% dos pacientes atingiram as recomendações de magnésio (5).Conclusão: Cada paciente deve ser avaliado individualmente, com ajuste da dieta as suas necessidades e condições clínicas. [resumo fornecido pelo autor]
Keywords: Hábitos alimentares; Cálculos biliares; Nutrição